The effects of genetic ablation of CaMKII oxidation on early ischemia-reperfusion arrhythmias in langendorff-perfused hearts. (10th June 2022) - Haugsten Hansen, M; Sadredini, M; Hasic, A; Anderson, ME; Sjaastad, I; Korseberg Stokke, M
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): South-Eastern Norway Regional Health Authority Introduction: Ventricular arrhythmias are common during the early phase of reperfusion after an ischemic event. Spontaneous diastolic release of Ca2+ from the sarcoplasmic reticulum (SR) contribute to arrhythmias in this stage, and reactive oxygen species (ROS) have been implicated in the process, through destabilization of key Ca2+ handling proteins. Specifically, ROS has been shown to activate the Ca2+/calmodulin-dependent protein kinase II (CaMKII), by oxidation of two methionines at positions 281/282 in the regulatory domain. This activation pathway contributes to Ca2+-dependent arrhythmia mechanisms in atrial fibrillation (AF), heart failure (HF) and diabetes. However, the role of oxidized CaMKII (Ox-CaMKII) in ventricular arrhythmias during early reperfusion has not been directly tested. We aimed to investigate the importance of ox-CaMKII for diastolic Ca2+ release events and arrhythmias in the early phase of reperfusion. Methods: We evaluated the propensity for early reperfusion arrhythmias in Langendorff-perfused hearts from mice carrying CaMKII resistant to oxidation (homozygous CaMKIIδ M281/282V mice) and wild type control mice (WT). The effect of beta-adrenoceptor stimulation, indirect inhibition of CaMKII via calmodulin antagonism, and antioxidant therapy was evaluated by the addition of isoprenaline, KN93 and N-acetylcysteine (NAC), respectively. Diastolic Ca2+ release events were recorded by confocal line scan imaging of isolated cardiomyocytes transiently exposed to hypoxia and ischemia-like conditions in the presence or absence of isoprenaline, and effects on Ca2+ handling proteins were assessed by immunoblotting. Results: Langendorff-perfused hearts from CaMKIIδ M281/282V mice showed no significant difference in the frequency of ventricular arrhythmias compared to WT during the early reperfusion phase, neither in absence, nor presence of beta-adrenoceptor stimulation with isoprenaline. The incidence of ventricular arrhythmias increased significantly upon beta-adrenoceptor stimulation but was prevented by the antioxidative agent NAC and reduced with CaMKII-inhibition with KN93 when tested in WT hearts. Immunoblotting of left ventricular tissue from perfused hearts revealed no significant differences in the abundance or phosphorylation levels of Ca2+-handling proteins. Ca2+ imaging experiments showed no differences between cardiomyocytes from CaMKIIδ M281/282V and WT mice with regard to incidence of spontaneous transients, Ca2+ waves or Ca2+ sparks, neither in absence, nor in presence of isoprenaline. Conclusions: This study demonstrates the importance of both ROS and CaMKII activation in the development of ventricular arrhythmias in the early phase of reperfusion. However, genetic ablation of CaMKII oxidation did not protect against early reperfusion arrhythmias, indicating that Ox-CaMKII is a not a critical factor in this process in Langendorff-perfused hearts.